The tragedy of Macbeth - Shakespeare, William 1564-1616 (United Kingdom : Sweet Cherry Publishing Limited, 2015)
Presents Shakespeare's drama about a man who kills the king of Scotland in order to claim the throne for himself, and includes explanatory notes, plot summaries, a key to notable lines and phrases, and other reference information.
Primary
800-899
Keywords: Shakespeare, William, -- 1564-1616; Macbeth, King of Scotland, active 11th century; English drama (tragedy); Regicides -- Juvenile literature; Drama -- Juvenile literature; Verse drama, English; Kings and rulers -- Juvenile literature; Scotland